Small-Angle X-Ray and Neutron Scattering on Photosynthetic Membranes - Jakubauskas, Dainius; Mortensen, Kell; Jensen, Poul Erik; Kirkensgaard, Jacob J. K. (Frontiers in Chemistry, 2021)
Ultrastructural membrane arrangements in living cells and their dynamic remodelling in response to environmental changes remain an area of active research, but is also subject to large uncertainty. The use of non-invasive methods as x-ray and neutron scattering provides an attractive complimentary source of information to direct imaging because in vivo systems can be probed in near-natural conditions. However, without solid underlying structural modelling to properly interpret the indirect information extracted, scattering provides at best qualitative information and at worst direct misinterpretations. Here we review the current state of small-angle scattering applied to photosynthetic membrane systems with particular focus on data interpretation and modeling.